PERHITUNGAN SUKU BUNGA EFEKTIF UNTUK PENENTUAN ALTERNATIF PEMBIAYAAN KENDARAAN MOTOR PADA LEASING DAN BANK DENGAN METODE INTERPOLASI LINIER (Studi Kasus Harga Sepeda Motor Honda Beat Injeksi Terdaftar Bulan September 2014) - Swasnita Swasnita; Suparti Suparti; Sugito Sugito (Jurnal Gaussian, 2015)
Imposition of interest rates by the bank and leasing in providing credit is different. The interest rate usually not included in the brochure loan installments. The calculation of the interest rate can be calculated using the flat rate and the effective interest rate. In the calculation of the effective interest rate can be performed using linear interpolation. Determination of the motorcycle financing alternative most favorable to the customer, can be seen from the lowest interest rates charged. The results of the case study Honda Beat injection prices listed September 2014 on credit motorcycle through leasing Central Sentosa Finance (CSF), leasing Adira Multifinance (Adira) and credit through Bank Rakyat Indonesia showed the lowest interest rate on the lease Central Sentosa Finance (CSF). In addition to low interest rates charged are other benefits that the filing procedures quickly and without collateral (guarantee). Keywords : Flat Interest Rate, Effective Interest Rate, Linear Interpolation, Leasing, Bank